Enhancing sustainable development through plant genetics - Ronald, Pamela C. (Nature reviews. Genetics, 2023)
In April 2023, scholars and experts met members of the US Congress for the Aspen Institute Congressional Program conference in Bellagio, Italy, to discuss strategies to ensure global food security. Building on her perspective from this meeting, Pamela Ronald highlights the role that plant genetics can have in achieving these goals. In April 2023, leading experts met with members of US Congress to discuss strategies to ensure global food security. Following on from this, Pamela Ronald emphasizes the role that plant genetics has in achieving these goals.